Boosting anionic redox of TiS4 via Se anion doping for high-performance Al-ion batteries - Junfeng Li; Yunshan Zheng; Kwan San Hui; Kaixi Wang; Chenyang Zha; Sambasivam Sangaraju; Xi Fan; Yanli Chen; Guangmin Zhou; Kwun Nam Hui (Next Energy)
Aluminum-ion batteries (AIBs) are gaining attention for large-scale energy storage due to their low cost and high theoretical capacity. However, the existing cathode materials frequently encounter rapid capacity degradation and sluggish reaction kinetics due to the strong interaction with high-charge Al3+, which limits the utilization of AIBs. Here, the Se-doping strategy is proposed to facilitate the active participation of anions in charge compensation and enhance the anionic redox process of amorphous anion-rich TiS4. A refined amount of Se doping effectively improves reaction kinetics for Al-storage and stabilizes the structure of the material, preventing polysulfide dissolution under high dealumination states. As a result, amorphous TiS3.5Se0.5 delivers unprecedented Al3+ storage performance, with a stable capacity of 210mAhg−1 at 500 mA g−1 over 400 cycles. Through detailed characterization, we reveal that a-TiS3.5Se0.5 undergoes reversible Al3+ insertion, accompanied by anionic redox processes involving S22- and Sen- species, which lays the foundation for further development of anionic-redox-based cathodes for high-performance AIBs.